Measurement of mass attenuation coefficient of paraffin wax by using low energy x-ray - Daud, Nurul Shazliana Mohamad (Universiti Sains Malaysia, 2024)
This study explores the mass attenuation coefficient properties of paraffin wax at kilovoltage x-ray energies and compares these properties with those of solid water phantom, water, and Perspex, which are commonly used to mimic human tissue. Using the Half-Value Layer (HVL) method, we determined the effective energies for 60, 81, and 125 kVp, finding values of 35.22, 37.57, and 41.20 keV, respectively. The results showed that mass attenuation coefficients were highest at lower effective energies and decreased with higher energies, consistent with the behaviour of the photoelectric effect. Besides, it was noted that the variation of x-ray transmission factor, ln (I0/I) was linear with the increased of phantom thickness. Additionally, we assessed the percentage deviations of the mass attenuation coefficients of solid water phantom, Perspex, and paraffin wax from those of water, emphasizing water's role as a reference material due to its radiological similarity to human tissues. The results obtained were validated against theoretical values from XCOM software, confirming the accuracy of our methods. Current study suggested that the maximum deviation of mass attenuation coefficient obtained experimentally in comparison to that of XCOM were 25% for water, 27% for Perspex, 8.4% for paraffin wax, and 44% for solid water phantom. This study supports the use of paraffin wax as a cost-effective tissue equivalent material for radiological applications and provides a solid foundation for future research and practical use in diagnostic radiology and quality assurance.